Work-related stress and cognitive enhancement among university teachers - Wiegel, Constantin (Anxiety, stress, and coping, 2016)
Background: Working conditions of academic staff have become increasingly complex and occupational exposure has risen. This study investigates whether work-related stress is associated with the use of prescription drugs for cognitive enhancement (CE). Methods: The study was designed around three web-based surveys (n1 = 1131; n2 = 936; n3 = 906) to which university teachers at four German universities were asked to respond. It assessed past CE-drug use and the willingness to use CE-drugs as factors influencing future use. Overlap among participants across the surveys allowed for analyses of stability of the results across time. Results: Our study suggests a currently very low prevalence of CE-drug use as well as a low willingness to use such drugs. The results showed a strong association between perceptions of work-related stress and all measures of CE-drug use (when controlling for potential confounding factors). They also showed that past use of CE-drugs increased participants' willingness to use them again in the future, as did lower levels of social support. Two different measures showed that participants' moral qualms against the use of CE-drugs decreased their probability of using them. Conclusions: The results increase our knowledge about the prevalence of CE-drug use and our understanding of what motivates and inhibits the use of CE-drug.